Ilias Latina : Text, Interpretation, and Reception - Schubert, Christoph,; Falcone, Maria Jennifer, (Mnemosyne, Supplements ;, 2021)
In Ilias Latina. Text, Interpretation, and Reception , the contributors approach this short poem, whose appeal and importance have not been sufficiently appreciated, from a multitude of scholarly perspectives. The challenging synthesis of the different issues shows that both a new edition and a modern literary interpretation of the poem are needed. Particularly focusing in various ways on the technique of vertere , the papers concern four main issues: the different elements of the narration, such as macro- and microstructure, single Bauformen and motifs, characters and scenes; the intertextual allusions to Homer and the texts of the Roman poetic tradition; the literary genre, the explicitly metaliterary passages and the implicit narrative and poetic choices; the medieval reception of the Ilias Latina.